App clusters: Exploring patterns of multiple app use in primary learning contexts. (December 2018) - Howard, Sarah K.; Yang, Jie; Ma, Jun; Maton, Karl; Rennie, Ellie
Abstract: There has been a continuous and rapid increase in the volume of apps in recent years since tablets became widely available in schools. Tablets contain a wide variety of apps, which are used for a large range of activities and tasks, and they are used in different combinations over time. Yet, there is limited research on young children's real and varied use of apps. The variety and volume of apps accessed by young children contributes to difficulty understanding there use and the consequences of that use. This has limited understanding of how apps contribute to students' learning. Given the importance of high-quality early learning experiences, it is essential that the use of apps in schools is better understood. This paper explores young children's real varied app use through a large aggregated Australian dataset of app usage in primary schools, which has been collected automatically from approximately 15, 000 Android devices over three years. The data mining methods of clustering and association rules analysis have been used to identify patterns of app use. Results show five distinct patterns of app use. Findings provide important insights into the complexity of multiple app use in the classroom. Implications of different use patterns in relation to learning and teaching are discussed. Highlights: Little is known about how students actually use apps to support learning. Five unique patterns of app use were identified from 148 schools. App use generally comprised 'drill and practice' apps which have limited effect on learning. Patterns show a shifting ratio of educational and non-educational apps. Patterns show unique emphases on different types of apps, which will impact on learning.